Genotypic diversity in the type and quantum of root exudates in Saccharum complex and allied genera - Vengavasi, Krishnapriya; E, Karpagam; Raja, Arun Kumar; Raju, Gomathi; Kookal, Chandran; Srinivasavedantham, Vasantha; Muthalagu, Alagupalamuthirsolai (Journal of Sugarcane Research, 2024)
Root exudates are implicated in biotic and abiotic stress resistance mechanism by influencing the rhizosphere microbiome, which also enhance the availability of fixed soil nutrients. The significance of root exudates is profoundly higher under adverse growing conditions in comparison to conducive environments. Several reports are available on the above-ground morpho-physiological adaptations to biotic and abiotic stresses, whereas exudation of root-released organic compounds is one of the least studied responses in sugarcane. Root exudates at the optimal amount determines crop establishment and survival by overall improvement in rhizosphere fitness and microbiome beneficial for nutrient acquisition. An attempt was made to characterise the diversity in root exudates of Saccharum spp. clones and allied genera under ambient growing conditions during the germination phase. Among the tested 40 genotypes, 26 were previously reported to be resistant against biotic and abiotic stresses, out of which 16 genotypes exhibited greater proportion of root-released organic compounds, which apart from other adaptive above-ground responses may attribute to their resistance mechanism. The data generated may aid future research in this field of work, and for optimal utilisation of genetic resources.